2021
DOI: 10.1002/col.22624
|View full text |Cite
|
Sign up to set email alerts
|

Visual color research of packaging design using sensory factors

Abstract: Package designs stimulate consumers visually and give rise to a sense of aesthetism, thus improving product visibility. In this study, emotions related to color combinations in packaging were addressed, cake packaging designs were tested, and affective design elements regarding styles and colors along with the diverse emotions that resulted were assessed and researched. Four experiments were conducted: Experiment 1 was on the affective characteristics related to types of colored boxes in packaging design; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…As far as the significance and characteristics of oil painting are concerned, it is very rich in color and very expressive. These elements are very important in nanofiber packaging design, so it is natural to integrate oil painting art into nanofiber packaging design [17]. When facing oil painting, the first information that the viewer can get is the color of the photo.…”
Section: Oil Painting Art and Nano Cellulose Packaging Designmentioning
confidence: 99%
“…As far as the significance and characteristics of oil painting are concerned, it is very rich in color and very expressive. These elements are very important in nanofiber packaging design, so it is natural to integrate oil painting art into nanofiber packaging design [17]. When facing oil painting, the first information that the viewer can get is the color of the photo.…”
Section: Oil Painting Art and Nano Cellulose Packaging Designmentioning
confidence: 99%
“…Based on literature review, the design factors of consumers' perceptions of packaging are identified, including packaging materials, visual attraction, functional technology, and brand attitude (Kuo et al, 2021;Lavuri et al, 2022;Orth & Malkewitz, 2008;Ritnamkam & Sahachaisaeree, 2012;Van Ooijen et al, 2017). In addition, the semantic evaluation of the cosmetic packaging design from 53 respondents was collected through user interviews to obtain the key factors of universal perception.…”
Section: Construction Of the Evaluation Index Systemmentioning
confidence: 99%
“…Willingness to buy is more related to the packaging graphic design than to the material [18]. The majority of research dealing with the impact of packaging on product purchases comes to the conclusion that color has a major impact on the product selection itself [15,17,23,26]. This research was extended to other variables (apart from color, which had a great influence on product selection) that could also influence product selection.…”
Section: Analysis Of Factors Influencing the Purchase Of Food Productsmentioning
confidence: 99%
“…In their research, Ahmad et al conclude that the packaging colors are the most important and significant features when purchasing a product [25]. Kuo et al also investigate what effect certain color combinations have on purchasing food products [26]. Li researches in his work the way to use new technologies and new methods in order to design interactive visual communication packaging design for the product [27].…”
Section: Introductionmentioning
confidence: 99%